Multifaceted Role of the Acellular Dermal Matrix in Novel Wound Healing: A Case Series - Naveen Narayan; Dharini Kishor; Yashas Hosur Ramegowda (Journal of Clinical and Diagnostic Research)
Acellular Dermal Matrix, Matriderm®, a collagen and elastin matrix, has emerged as a versatile tool in wound coverage, promoting healing and reducing scarring, thus offering numerous advantages in various clinical scenarios. The varied uses demonstrated here include concomitant application of the acellular dermal matrix while grafting with a full-thickness skin, application over bare bone in Split-Thickness Skin Grafting (STSG) and in the treatment of mucocutaneous fistulae in the oral cavity. The outcome with the use of Matriderm® in all these cases was satisfactory. Hereby, the authors present a case series of four patients that provide an understanding of Matriderm®’s efficacy in promoting healing and regeneration in complex wounds. Matriderm®, an acellular dermal matrix composed of collagen and elastin, supports tissue regeneration and reduces scarring, making it a valuable tool in complex wound management. The present case series highlights its versatility and potential in advancing wound care.